2010
DOI: 10.1111/j.1468-2389.2010.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Individual Differences on the Perceived Job Relatedness of a Cognitive Ability Test and a Multimedia Situational Judgment Test

Abstract: Although there is a growing number of publications concerning applicant reactions to different selection instruments, the relationships between individual differences and applicant reactions have largely remained unexplored. The aim of the present study was to examine the effects of several testing-related and general individual differences (anxiety, self-evaluations, and personality) on the most commonly studied dimension of applicant reactions, namely the perceived job relatedness of selection instruments. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 67 publications
3
40
2
Order By: Relevance
“…The findings of yet other studies (e.g., Oostrom, Born, Serlie, & Van Der Molen, 2010;Potosky & Bobko, 2004;Sylva & Mol, 2009;Wiechmann & Ryan, 2003) showed that reactions to computerized tests depend on a host of other factors (e.g., computer anxiety, computer self-efficacy, test-taking experience or self-efficacy). Several of these factors are considered below in a subsection that focuses on adverse impact.…”
Section: Applicant Acceptance Of Electronic Tests and Personality Invmentioning
confidence: 94%
“…The findings of yet other studies (e.g., Oostrom, Born, Serlie, & Van Der Molen, 2010;Potosky & Bobko, 2004;Sylva & Mol, 2009;Wiechmann & Ryan, 2003) showed that reactions to computerized tests depend on a host of other factors (e.g., computer anxiety, computer self-efficacy, test-taking experience or self-efficacy). Several of these factors are considered below in a subsection that focuses on adverse impact.…”
Section: Applicant Acceptance Of Electronic Tests and Personality Invmentioning
confidence: 94%
“…This is surprising considering the widespread use of interviews in selection (Salgado et al 2001). Applicant personality traits and selection methods may interact so that relationships between traits and reactions do not generalize from one selection tool to another (Merkulova et al 2014; Oostrom et al 2010). It is therefore important to study relationships between applicant personality and fairness reactions also in the context of interviews.…”
Section: Introductionmentioning
confidence: 99%
“…The idea here is that, regardless of what an employer does, some applicants will be negatively or positively predisposed to the selection procedures and the selection system, depending on what personal characteristics they bring to the situation. Researchers have continued to examine personality traits of job applicants for their effects on applicant reactions (e.g., Honkaniemi, Feldt, Metsäpelto, & Tolvanen, 2013;Oostrom et al, 2010). Positive and negative affectivity also have been found to affect the relationship between justice and outcomes such as recommendations and litigation intentions .…”
Section: Individual Differencesmentioning
confidence: 99%
“…This theoretical expansion has advanced our knowledge about the mechanisms underlying applicant reactions. Third, researchers have expanded the focus of applicant reactions research beyond perceptions of justice to include additional test-taking reactions, such as test-taking motivation, anxiety, and efficacy (Lievens, De Corte, & Brysse, 2003;Oostrom, Born, Serlie, & van der Molen, 2010), with a corresponding expansion of underlying theories, such as cognitive interference (McCarthy et al, 2013). Finally, there has been increased effort to bridge the gap between theory and practice by developing techniques to mitigate negative reactions, such as incorporating feedback explanations to candidates (e.g., Truxillo, Bauer, Campion, & Paronto, 2002).…”
Section: Research Trend 1: Expansion Of the Theoretical Lensmentioning
confidence: 99%
See 1 more Smart Citation